Efficacy of hexaconazole for the control of white rust on chrysanthemum and powdery mildew on roses - Lam, C.H.; Lim, T.K. (Informa UK Limited, 1993)
THexaconazole, a new triazole fungicide, and its mixture with protectant fungicides, were evaluated for their efficacy as weekly foliar sprays to control white rust (Puccinia horiana) of chrysanthemum and powdery mildew (Sphaerotheca pannosa) of roses. Hexaconazole at 50 μg/ml gave excellent control of both white rust and powdery mildew. It was superior to the standard fungicides, triadimefon at 125 μg/ml for white rust and triforine at 300 μg/ml for powdery mildew. The mixtures of hexaconazole with captan (1:17.5) and with mancozeb (1:28) were also highly effective for controlling white rust on chrysanthemum. No undesirable phytotoxic effects were evident on chrysanthemum and rose plants treated with hexaconazole or its mixtures. The effective control of these diseases is of benefit not only to local growers but also to foreign importers from countries which enforce stringent quarantine measures.